2014
DOI: 10.1186/s13613-014-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula: recommendations for daily practice in pediatrics

Abstract: High-flow nasal cannula (HFNC) is a relatively new device for respiratory support. In pediatrics, HFNC use continues to increase as the system is easily set up and is well tolerated by patients. The use of nasal cannula adapted to the infant’s nares size to deliver heated and humidified gas at high flow rates has been associated with improvements in washout of nasopharyngeal dead space, lung mucociliary clearance, and oxygen delivery compared with other oxygen delivery systems. HFNC may also create positive ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 51 publications
3
123
0
6
Order By: Relevance
“…Although the criteria for ICU admission are variable 16,34 and those for HFNC have not yet been established, 35 these escalated care interventions are generally limited to children with hypoxia and concern respiratory distress. 30 We did not include isolated use of intravenous or nasogastric hydration or supplemental oxygen in this definition because some institutions use intravenous or nasogastric hydration routinely on admission, 18 and the criteria for supplemental oxygen are disparate.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although the criteria for ICU admission are variable 16,34 and those for HFNC have not yet been established, 35 these escalated care interventions are generally limited to children with hypoxia and concern respiratory distress. 30 We did not include isolated use of intravenous or nasogastric hydration or supplemental oxygen in this definition because some institutions use intravenous or nasogastric hydration routinely on admission, 18 and the criteria for supplemental oxygen are disparate.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…It also allows the administration of variable fraction of inspired oxygen (FiO 2 ) by minimising entrainment of room air. Flow rates described as constituting high flow are variable, ranging from 1 to 2 L/kg/min, with some evidence that higher flow rates deliver higher positive airway pressure,8 9 and that air leak around the nares and mouth opening significantly affect delivered pressure 10. There is currently limited evidence to support the efficacy and safety of HFNC for its use as a form of respiratory support in the treatment of the variety of indications for which it is currently used 7.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in pediatric patients younger than 6 months, pharyngeal pressure was increased as flow increased, and at a level of 7 L/min the mean pressure and PEEP pressure were elevated to 4 and 6.5 cmH 2 O, respectively 9 . Furthermore, when humidified and heated oxygen-air mixture was Fraction of inspired oxygen administered to trachea, upper airway resistance was also reduced 10 .…”
Section: Discussionmentioning
confidence: 97%